Validation of ICNP® Nursing Diagnoses for assistance to women during postpartum - Walnizia Kessia Batista Olegário; Leiliane Teixeira Bento Fernandes; Cláudia Maria Ramos Medeiros (Universidade Federal de Goias, 2015)
The nomenclature validation contributes in the care provided by Nursing, stimulating and directing necessary changes for the quality improvement of attention to woman's health. The study aimed to validate affirmatives of ICNP® Nursing Diagnoses for nursing assistance to women during postpartum. This is a methodologic study composed by three steps: affirmative selection, semantical analysis and Index of Agreement calculation. The sample was composed by 12 experts in Obstetric Nursing and used an instrument with items of interest for this study. Thirty (88,23%) ICNP® Nursing Diagnoses were assessed, and only four were not validated. The study found the need to investigate and update ICNP® terms permanently. Besides, the proposal and tendency of using electronic records in health institutions points to the need to validate, standardize, and legitimize Nursing Diagnoses for clinical practice.